Adultos maduros na educação profissional e tecnológica: um estudo à luz da diversidade geracional - Silveira, Juliane Vanessa Rippel (2021)
The aging process in the educational scenario is an issue that needs studies and discussions, since it is intrinsic to the human being. In addition, population aging is a global phenomenon and has been manifesting rapidly, bringing great challenges to public policies, including education. In order to prepare the subjects for the needs of the world of work, considering the generational context, the importance of promoting an innovative education is highlighted. In this sense, this study aimed to analyze the teaching process in Professional and Technological Education (EPT), in the generational context, with a focus on the mature adult student, seeking to understand who this student is, what are his expectations when seeking EPT and how the intergenerational relationship takes place in the classroom. The emphasis on the diversity of generations in EFA classes is justified by the fact that, as professional education has been transformed to meet the demands of the world of work, the profile of the student and the school have also changed, but the productions and research scientific studies aimed at vocational and technological education are still incipient. To determine the expression “mature adult”, the theory of Erik Homburger Erikson (1976), Juán José Muriño Mosquera and Claus Stobäus (1983), Juán José Muriño Mosquera (1987) and Helena Beatriz Finimundi Balbinotti (2003; 2005; 2007 and 2012), starting from the definitions of their theories about the phases of life, which will be presented in the following sections. This is a cross-sectional, exploratory study, using questionnaires for data collection and a qualitative approach, treated in a descriptive perspective, since it considers the subjectivity of the participating subjects and interpreted through reports provided by them. In conclusion, it is believed that the great ideal of education should be based on pedagogical practices consistent with the reality of each student. Considering that a person in adulthood has had several experiences, both in personal and professional life, it is expected that he / she will have facilities to make associations for certain subjects, difficulties in understanding others and interest aroused in something that is related to their day to day. day, to your living environment or at any point that has aroused your curiosity. It also highlights the importance of the teacher's role, to get to know his students, their expectations and to encourage them for the permanent search for knowledge, personal fulfillment and overcoming their needs, thus allowing a greater number of people achieve positive trajectories. It should be added that the results show that mature adult students experience situations more deeply according to their life experiences, that is, due to the baggage of knowledge acquired on a daily basis, therefore, these particular situations should serve as a basis for the new personal constructions that learning can point out.